Consensus statement: botulinum toxin in myofacial pain - Reilich, Peter; Fheodoroff, Klemens; Kern, Kai-Uwe; Mense, Siegfried; Seddigh, Susann; Wissel, Jörg; Pongratz, Dieter (Journal of neurology, 2004)
No Abstract available for this article.
Gesehen am 07.09.2017